An Innovative Strategy for the Green Synthesis of Nanochitosan Using Plant Extracts and Their Possible Applications: A Review - Riki, Riki; Ahmad, Islamudin; Herman, Herman; Ibrahim, Arsyik; Rusman, Arman; Samsul, Erwin; Rusli, Rolan; Arifuddin, Muhammad; Junaidin, Junaidin; Bone, Mahfuzun; Rijai, Hifdzur Rashif; Hikmawan, Baso Didik (Universitas Gadjah Mada, 2025)
The numerous applications of nanochitosan in a variety of sectors, including medicine, food, and agriculture, attract researchers to work toward the development of environmentally favorable, safe, and efficient synthesis methods. Currently, a biological approach is being developed to synthesize nanochitosan to address the limitations of conventional methods. The synthesis of biogenic pathways employs biological entities, including plant extracts and microorganisms, as nanoparticle-forming agents. The use of extracts is more desirable due to the simple working procedure, the absence of hazardous chemicals, the economic benefits, and the use of basic equipment. This article highlights the role of biomolecules in plant extracts, including polyphenols, terpenoids, citric acid, alkaloids, and polysaccharides, in the synthesis of nanochitosan. Nanoparticle preparation protocols and characterization using zeta potential analysis techniques, scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy, and Fourier transform infrared spectroscopy (FTIR) are briefly described. The potential applications of green nanochitosan are also discussed, considering the results of biological activity testing and the potential mechanisms associated with these activities. According to the results of numerous studies highlighted in this review, nanochitosan synthesis utilizing plant extracts appears to be a promising alternative approach to conventional methods.